Beyond the National Open Science Sphere: Organising the ERUA Open Science Live Meet-Ups - Maximilian Heber; Goran Sekulovski (Liber Quarterly: The Journal of European Research Libraries)
The Open Science Community reaches beyond national borders, which entails the necessity of international exchange to learn from each other and to develop measures jointly. But how to implement formats of exchange? In this report, Maximilian Heber and Dr. Goran Sekulovski share their experiences planning and performing the ERUA Open Science Live Meet-Ups, a low-threshold format of exchange implemented whitin the European Reform Universities Alliance (ERUA), an alliance of the European Universities Initiative (EUI). Doing so, they reflect critically on this format, hoping that this paper may be a resource of inspiration for others who may be interested in setting up similar initiatives.